(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
Three organic phosphorous compounds containing bridge with (PhO) phenoxide and (Ph) phenyl group, to be used as materials derived element cadmium ion according to the (liquid - liquid) extraction method that apply to widely used in the restoration of metal ions operations starting from aqueous solutions in mining operations to environmental applications, and identified some of the physical properties (melting point, spectra UV, IR). Photometric method was adopted to determine the concentrations, as it used the solution of 2-Nitroso, 1- Naphthol to determine the concentrations of cadmium ion in the aqueous phase after extraction and its concentrations in the organic phase based on the difference between the concentrations of primitive prepared aqueous solution and the final concentrations in the aqueous phase. Distribution Ratio DCd was studied of the ion cadmium between the aqueous medium of the acid solution of Sulfuric and central Organic Dilutions containing different concentrations of the previous prepared organophosphorus compounds also was studied the Distribution Ratio DCd of ion cadmium depending of changing of pH-values in aqueous medium and central organic Includes fixed concentration from the previous prepared organophosphorus compounds and registered the distribution of information focus numerically and graphically.